M-learning adequacy and perceptions of students and teachers in secondary schools - Ozdamli, Fezile; Uzunboylu, Huseyin (British journal of educational technology, 2015)
In recent years, the use of mobile technologies has increased in a number of fields such as banking, economy, tourism, entertainment, library research, etc. These developments have also led to the use of mobile technologies for educational purposes. The successful integration of mobile learning (m‐learning) technologies in education primarily demands that teachers' and students' adequacy and perceptions of such technology should be determined. Therefore, the aim of this study was to compare teachers' and students' abilities and perceptions concerning m‐learning. Research data for the analysis were obtained from a sample of 467 teachers and 1556 students from 32 schools that were surveyed in Northern Cyprus. Based on our results, we conclude that teachers and students want to use m‐learning in education. Their perceptions are positive but their m‐learning adequacy levels are not sufficient.